2023
DOI: 10.3390/met13050909
|View full text |Cite
|
Sign up to set email alerts
|

Novel Cast and Wrought Al-3Zn-3Mg-3Cu-Zr-Y(Er) Alloys with Improved Heat Resistance

Abstract: The main weaknesses of commercial high-strength Al-Zn-Mg-Cu-based alloys are the low casting properties, corrosion and heat resistance. Al-Zn-Mg-Cu-based alloys with Zn/Mg ratio equal to 1 combine good strength, corrosion and heat resistance. Al alloys with atomic ratio Cu/Y(Er) equal to 4 have a narrow solidification range and high solidus temperature. Two basic principles were taken into consideration to develop novel heat-resistant Al-Zn-Mg-Cu-based alloys with improved casting properties: 1—mass ratio of Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 47 publications
1
18
0
Order By: Relevance
“…Micro-alloying serves as an effective approach for modifying the microstructure and improving the properties of Al-Zn-Mg-Cu alloys [10]. Previous studies have demonstrated that the trace addition of Sc [11,12], Er [13,14], and Ag [15,16] has positive effects on the strength and corrosion resistance of Al-Zn-Mg-Cu alloys. However, the high price of these alloying elements hinders the widespread industrial application.…”
Section: Introductionmentioning
confidence: 99%
“…Micro-alloying serves as an effective approach for modifying the microstructure and improving the properties of Al-Zn-Mg-Cu alloys [10]. Previous studies have demonstrated that the trace addition of Sc [11,12], Er [13,14], and Ag [15,16] has positive effects on the strength and corrosion resistance of Al-Zn-Mg-Cu alloys. However, the high price of these alloying elements hinders the widespread industrial application.…”
Section: Introductionmentioning
confidence: 99%
“…A novel crossover Al-5.64Mg-5.43Zn-0.51Cu alloy with ultra-high strength was developed based on Al-Mg/Al-Zn-Mg-(Cu) systems [13]. A significantly earlier method of improving of casting properties and heat and corrosion resistance of the Al-Zn-Mg-(Cu) alloys was suggested [18][19][20][21]. This method was based on obtaining alloys with a Zn/Mg ratio near [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…A significantly earlier method of improving of casting properties and heat and corrosion resistance of the Al-Zn-Mg-(Cu) alloys was suggested [18][19][20][21]. This method was based on obtaining alloys with a Zn/Mg ratio near [18][19][20][21]. Novel cast and wrought Al-3Zn-3Mg-3Cu-Zr-Y(Er) alloys with improved heat resistance were developed based on the principles of the Zn/Mg ratio [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This solubility sharply decreases with cooling, resulting in the precipitation of metastable precursors of MgZn 2 and/or Al 2 Mg 3 Zn 3 phases. For example, this effect was successful in AA7xxx alloys based on the Al-Zn-Mg system [25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%